Enhancing Visuomotor Adaptation by Reducing Error Signals: Single-step (Aware) versus Multiple-step (Unaware) Exposure to Wedge Prisms - Michel, Carine; Pisella, Laure; Prablanc, Claude; Rode, Gilles; Rossetti, Yves (Journal of cognitive neuroscience, 2007)
Neglect patients exhibit both a lack of awareness for the spatial distortions imposed during visuomanual prism adaptation procedures, and exaggerated postadaptation negative after-effects. To better understand this unexpected adaptive capacity in brain-lesioned patients, we investigated the contribution of awareness for the optical shift to the development of prism adaptation. The lack of awareness found in neglect was simulated in a multiple-step group where healthy subjects remained unaware of the optical deviation because of its progressive stepwise increase from 2° to 10°. We contrasted this method with the classical single-step group in which subjects were aware of the visual shift because they were directly exposed to the full 10° shift. Because the number of pointing trials was identical in the two groups, the total amount of deviation exposure was 50% larger in the single-step group. Negative after-effects were examined with an open-loop pointing task performed with the adapted hand, and generalization was tested with open-loop pointing with the nonexposed hand to visual and auditory targets. The robustness of adaptation was assessed by an open-loop pointing task after a simple de-adaptation procedure. The progressive, unaware condition was associated with larger negative after-effects, transfer to the non-exposed hand for the visual and auditory pointing tasks, and greater robustness. The amount of adaptation obtained remained, nevertheless, lower than the exaggerated adaptive capacity seen in patients with neglect. Implications for the functional mechanisms and the anatomical substrates of prism adaptation are discussed.